Community volunteer assessment of recreational water quality in the Hutt River, Wellington. Issue 2 (2nd April 2020) - Valois, Amanda E.; Milne, Juliet R.; Heath, Mark W.; Davies-Colley, Rob J.; Martin, Emily; Stott, Rebecca
ABSTRACT: Water is an important component of many recreational opportunities and New Zealand invests significant resources in recreational water quality (RWQ) monitoring to assess risks to public health. However, monitoring primarily focuses on microbiological hazards and RWQ is considerably broader than this. The goal of this study was to take a comprehensive approach to evaluating RWQ while exploring the potential for greater public involvement in monitoring. A popular river swimming site was co-monitored weekly by volunteers and a council field officer. The attributes monitored–water temperature, visual clarity, benthic cyanobacteria and filamentous periphyton cover, E. coli and rubbish–were identified from a volunteer workshop. There was good concordance between volunteer and council data suggesting that volunteer measurements can be considered reliable. This highlights the potential for volunteers, with professional support, including training and quality assurance, to extend council RWQ surveillance to additional monitoring sites while improving public engagement on water management.